A safe return to sport and the right to play during COVID-19 - Costello, F. E.; Duggan, K.; Lang, E.; Norris, S. (Canadian Medical Association Journal, 2021)
In 2018, the World Health Organization (WHO) launched a global action plan targeting a 15% reduction, by 2030, in insufficient physical activity among adolescents.1 This initiative was prompted by the discovery that 80% of youth were not meeting recommendations for daily physical activity.1 Accordingly, the WHO called for an urgent "scaling-up" of programs aimed at increasing physical activity and reducing screen time. Unfortunately, the coronavirus disease 2019 (COVID-19) pandemic has thwarted these efforts. Surveys of 2426 children from Shanghai, China, showed a reduction in physical activity of 7 hours per week and a corresponding increase in screen time of 30 hours per week, when comparing activities before and after implementation of pandemic restrictions. The implications are dire, because prolonged screen time has been linked to depression and anxiety among youth. In fact, 64% of teenagers surveyed in a national youth development organization in the United States indicated that COVID-19 will have a lasting effect on their generation`s mental health. Public health measures must therefore balance the effects of pandemic restrictions against the risks of viral transmission among children.